Relationship Between Fiber in Diet and Acute Appendicitis (Medical Forum Monthly, 2020)
Objective: To determine the relationship of fiber in diet and other socio-demographic factors with acute appendicitis among adult population of Rawalpindi.Study Design: Case control studyPlace and Duration of Study: This study was conducted at the Department of Surgery & histopathology of Benazir Bhutto Hospital and Isra University Medical College Islamabad for two years from Jan 2018 to Jan 2020.Materials and Methods: Two hundred patients operated for acute appendicitis and confirmed by histopathology report were included in the study along with equal number of age and gender matched controls from the community. Detailed dietary history was obtained with the help of structured questionnaires to calculate the amount of fiber in diet of both the cases and controls. Level of fiber in diet, Body mass index, family income and presence of co morbid diseases were compared among the cases and controls with chi-square. Mean dietary fiber in grams was also compared among the cases and controls by student-t test.Results: Out of 200 confirmed cases with acute appendicitis, 123 (61.5%) showed the presence of low dietary fiber while 73 (38.5 %%) had adequate or high dietary fiber. Among the healthy controls 91 (45.5%) showed the presence of low dietary fiber while 109 (54.5%) had adequate or high dietary fiber (N=400). Mean age of the cases was 30.5±2.15 years and of the controls was 30.3±3.311 years. After applying the chi-square, we found that amount of dietary fiber and family income had significant difference among the cases and controls (p-value<0.05). Mean dietary fiber in grams among the cases was 22.6±2.12 grams while for the controls was 32.7±2.91 grams (p-value <0.05).Conclusion: Low dietary fiber emerged as predictor of acute appendicitis as it was significantly present in the cases confirmed with acute appendicitis as compared to controls. In addition to dietary fiber low family income also had a significant relationship with the presence of acute appendicitis among the cases.